2020
DOI: 10.3389/fonc.2020.00927
|View full text |Cite
|
Sign up to set email alerts
|

The Circumferential Resection Margin Is a Prognostic Predictor in Colon Cancer

Abstract: Objective: This study aimed to investigate the potential value of circumferential resection margin (CRM) in colon cancer prognostics. Summary Background Data: CRM has been extensively studied as an important prognostic factor in rectal and esophageal cancer, but not in colon cancer. Methods: Data from 6,681 CRM-positive patients and 25,908 CRM-negative patients diagnosed with colon cancer in 2010–2015 were obtained from the Surveillance, Epidemiology, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…Amri et al initially confirmed the prognostic significance with CRM involvement in colon cancer in 2015, identifying it as an independent prognostic factor linked with reduced OS (HR 3.39 p < 0.001), reduced DFS (HR 2.03 p < 0.001), and higher rates of recurrence (HR 3.32 p < 0.001) [ 253 ]. These findings are confirmed in a large population study by Tang et al in 2020, which found that patients with a CRM value of 0–30 mm benefited most from chemotherapy [ 255 ]. Evidence on the optimal CRM in both rectal and colon cancer is inconsistent.…”
Section: Pathological Featuressupporting
confidence: 59%
See 3 more Smart Citations
“…Amri et al initially confirmed the prognostic significance with CRM involvement in colon cancer in 2015, identifying it as an independent prognostic factor linked with reduced OS (HR 3.39 p < 0.001), reduced DFS (HR 2.03 p < 0.001), and higher rates of recurrence (HR 3.32 p < 0.001) [ 253 ]. These findings are confirmed in a large population study by Tang et al in 2020, which found that patients with a CRM value of 0–30 mm benefited most from chemotherapy [ 255 ]. Evidence on the optimal CRM in both rectal and colon cancer is inconsistent.…”
Section: Pathological Featuressupporting
confidence: 59%
“…CRM positivity occurs in 7.3% to 25% of rectal cancers and 5.3% to 20.5% of colon cancers. It is associated with advanced stage, aggressive tumour grade, infiltrating tumour border, and lymphovascular and perineural invasion [ 253 , 255 ]. In rectal cancer, CRM positivity is a strong predictor of recurrence and reduced survival, independent of TNM staging [ 252 , 256 , 257 , 258 , 259 ].…”
Section: Pathological Featuresmentioning
confidence: 99%
See 2 more Smart Citations
“…For the development and popularization of complete mesorectal excision (CME) surgery in China, the scope of surgical resection is more thorough than that of traditional radical surgery, significantly improving the surgery quality. On the contrary, the CRM of some deeply infiltrated cancer tissues may still be negatively affecting the correct evaluation of the CRM [ 9 ].…”
Section: Introductionmentioning
confidence: 99%